2016
DOI: 10.3109/02770903.2016.1156693
|View full text |Cite
|
Sign up to set email alerts
|

Does urban extent from satellite images relate to symptoms of asthma, rhinoconjunctivitis and eczema in children? A cross-sectional study from ISAAC Phase Three

Abstract: In this study, the prevalence of symptoms of asthma, rhinoconjunctivitis and eczema in children were not associated with urbanisation, according to the land cover definition of urban extent from satellite data. Comparable standardised definitions of urbanisation need to be developed so that global comparisons can be made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Of the 18 studies, data were collected in 10 countries. Of note, one multinational study analyzing data from 237 worldwide centers in the ISAAC Phase Three Study was not shown in this figure 55 . See Table S2 for additional details.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 18 studies, data were collected in 10 countries. Of note, one multinational study analyzing data from 237 worldwide centers in the ISAAC Phase Three Study was not shown in this figure 55 . See Table S2 for additional details.…”
Section: Resultsmentioning
confidence: 99%
“…Satellite data now allow the study of green space exposure and land cover in much more detail. We identified two studies where this has been looked at in the context of AD, neither of which found evidence that green space exposure or land cover was associated with AD prevalence 54,55 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The assessment of this paper, when using the local administrative boundary provided in the portal found that it is not integrated with the global coordinate system. GADM usually be utilized for ArcGIS, and similar software is a spatial database that contains the location of the world's administrative boundaries [11]. GADM also a highresolution and open-source database which is available for academic purpose as well as for other non-commercial utilization.…”
Section: A Packagesmentioning
confidence: 99%